Monochamus galloprovincialis (Olivier, 1795)(Coleoptera: Cerambycidae), comportamiento y distancias de vuelo - hernandez, R.=700 1 Ortiz, A.; Perez, V.; Gil, J.M.; Sanchez, G.
(Es, En)
Ilus; 18 ref.
Keywords: BURSAPHELENCHUS XYLOPHILUS; NEMATODA; MADERA DE CONIFERAS; FEROMONAS; PINUS NIGRA; PINUS PINASTER; PINUS SYLVESTRIS; VECTORES; MONOCHAMUS; COMPORTAMIENTO; VUELO; ESPAÑA; BOLETIN DE SANIDAD VEGETAL: PLAGAS